Autosintonia de controladores PI para malha de corrente de uma máquina à relutância variável - Lima, Rousseau Saraiva Guimarães (2006)
This work has as objective to drive of a the variable reluctance machine with current loop, controlled through a controller PI (Proportional Integral). The parameters of the controller are auto-tuning through of one technique of identification using the method of relay. A great number of auto-tuning methods can be found in literature, which if they mainly differentiate for the amount of required information. In the case of the method developed in this work, a strategy searched that requested one reduced number of parameters keeping the amount of necessary information for auto-tuning of the controller. The auto-tuning implemented in this work is based on the method relay reference, in which to get the critical parameters of the process presumes the generation of symmetrical oscillations (cycles limits) during the feeding the relay. This type of applied methodology the identification of processes, assures the integrity of the drive system, besides having as main advantage its simplicity of execution. How much to the methods of tuning of controller PI of the current loop. The traditional method of auto-tuning is implemented whose the parameters had been gotten by Ziegler-Nichols, and a method modified in the direction to become more flexible the specifications given for phase and gain for the closed loop. The implementation of the algorithm of controller PI was elaborated in language C, with a hardware structure type computer, thus including a board of developed acquisition and a converter asymmetric half bridge, responsible for the direct feeding of the phases of the machine according to a keying strategy. They are presented resulted experimental of the drive system.